IMPLEMENTASI NILAI KEPESANTRENAN DALAM PERENCANAAN MADRASAH BERBASIS ASESMEN KEBUTUHAN DI MTs UBUDIYAH - Misda Ariyani; Ahmad Salabi; Yahya Mof (STKIP Subang, 2026)
This study aims to analyse the implementation of pesantren values in needs-based madrasah planning at MTs Ubudiyah. This study employs a qualitative approach using a case study design. Data collection was conducted through interviews, observation and documentation. The research subjects included headteachers of madrasahs, deputy headteachers responsible for student affairs, teachers, and religious activity coordinator. The findings of this study indicate that the pesantren values implemented include discipline, responsibility, cooperation, simplicity, honesty, and respect. Needs assessment was carried out in a participatory manner through regular coordination meetings and served as the basis for setting programme priorities as well as the RKM and RKAM documents. The implementation of pesantren values is also integrated into the vision and mission, annual work programmes, classroom learning, and the overall madrasah culture. Consequently, the implementation of pesantren values in madrasah planning based on needs assessment at MTs Ubudiyah has implications for strengthening religious culture, improving transparent and accountable madrasah governance, character-based curriculum innovation, enhancing the quality of graduates with noble character, and fostering public trust in the madrasah.